Streamer‐to‐precursor transition in N2–SF6 mixtures under positive repetitive submicrosecond pulses. (7th June 2021) - Zhao, Zheng; Dai, Zhifeng; Sun, Anbang; Li, Jiangtao
Abstract: The evolution of discharge dynamics in N2 –SF6 mixtures under long‐term repetitive submicrosecond pulses is investigated based on pulse‐sequence resolved electrical and optical diagnostics. The effects of gas pressure, pulse repetition frequency (PRF), and SF6 concentration on discharge evolutions are determined. The number of applied pulses before breakdown is shown to non‐linearly decrease with increasing PRF for all included gas pressures and SF6 concentrations. A higher SF6 concentration is favourable for increasing relative insulation capability under repetitive pulses. Unexpected complexities of discharge evolutions under repetitive pulses are reported for the first time for the discharge mechanism transition when a strong electronegative gas is introduced. A pulse‐to‐pulse progressive streamer (first discharge)‐to‐precursor (before breakdown) transition is observed in an N2 –SF6 mixture under positive repetitive pulses and is less dependent on gas pressure than traditional scenarios. The formation of a precursor section is jointly supported by electrical and optical signatures. The discharge mechanism transition and the detour phenomenon under repetitive pulses are discussed based on the effects of space charges on the spatial distribution of the electric field strength.